Amphipods from the Wallaby-Zenith Fracture Zone, Indian Ocean: new genus and two new species identified by integrative taxonomy. Issue 1 (2nd January 2020) - Weston, Johanna N. J.; Peart, Rachael A.; Jamieson, Alan J.
Abstract : The Wallaby-Zenith Fracture Zone, within the Wharton Basin of the East Indian Ocean, is a geomorphologically complex structure with depths from abyssal to hadal (∼6600  m) with limited published taxonomic data. To fill this knowledge gap, this study describes two new species of scavenging amphipods, Stephonyx sigmacrus sp. nov. (Uristidae) and Civifractura serendipia gen. et sp. nov. (Alicellidae), collected using baited traps from a depth of 4932  m. As identification of deep-sea amphipods is challenged by phenotypic plasticity and convergent evolution, we combined a morphological with a molecular phylogenetic analysis of two mitochondrial (16S rDNA and COI) and two nuclear (Histone 3 and 28S rRNA) regions, where possible (no genetic material was obtainable from S. sigmacrus sp. nov.). The genetic data uncovered cryptic taxonomy and elevated diversity within the non-monophyletic Alicellidae family and provided evidence for establishing a new genus. Additionally, we identified morphological variations from the Tectovalopsis wegeneri description, genetically resolved two previously identified specimens of Diatectonia sp. as T. wegeneri, and identified two new species of Tectovalopsis for future description. These investigations highlight the application of integrative taxonomic approaches and represent a potential model for resolving incongruent morphological and molecular phylogenies for deep-sea amphipods and other specimen-limited taxa. Paper – zoobank.org:pub:79BC3A33-4FB2-404B-B7CB-EC401B392817 Civifractura – zoobank.org:act:E513D9AB-C258-4079-B192-BB453D7F0CBA Civifractura serendipia – zoobank.org:act:B7110CA9-365C-4D0A-899D-5BFFDAD4A05E Stephonyx sigmacrus – zoobank.org:act:DDAB1B8D-8359-49FE-B1C7-42E10CE7C9F8